Synthesis and Characterization of Novel 1,3,4-Oxadiazole Derivatives Containing 5-(2,4-Dichlorothiazole) Substitute - Ghodsie, Shahram; Pourm, Sara; Rabiee, Samaneh; Shafiee, Abbas (Asian Journal of Chemistry, 2010)
2-[(2,4-Dichlorothiazol-5-yl)methylene]hydrazinecarboxamide (4) was obtained from the reaction of 2,4-dichlorothiazole-5-carboxaldehyde (2) and semicarbazide (3). 2-Amino-1,3,4-oxadiazole compound (5) was synthesized via the cyclization of compound 4 in the presence of bromine. Diazotation of compound 5 in hydrochloric acid in the presence of copper powder results compound 6 in which the amino group was substituted with chlorine. All the synthesized compounds were characterized by IR, Mass, 1H NMR or 13C NMR spectra and elemental analysis.